ESG IMPLEMENTATION ON FINANCIAL PERFORMANCE IN INDONESIA STUDY LITERATURE REVIEW - Chairunnisa, Widya Zahra; Yusnidar, Yusnidar; Fuadah, ⁠Lukluk (Musytari : Jurnal Manajemen, Akuntansi, dan Ekonomi, 2024)
In the era of globalization, Environmental, Social, and Governance (ESG) has become an essential framework for business decision-making and investment, especially in emerging markets like Indonesia. This study aims to analyze the impact of ESG implementation on financial performance in Indonesian companies through a literature review approach, focusing on recent research examining the correlation between ESG practices and financial outcomes. Using a comprehensive analysis of prior studies, this research explores the influences of ESG on profitability, market value, risk management, and operational efficiency, with attention to moderating factors such as digitalization. Findings indicate that robust ESG practices positively correlate with improved Return on Assets (ROA), increased market valuation, and reduced business risk, supported by enhanced transparency and stakeholder trust. Digitalization strengthens the link between ESG initiatives and financial performance by facilitating efficient data management and compliance. This research concludes that ESG is a tool for risk mitigation and a sustainable growth strategy for companies in Indonesia.